ANALISIS STRUKTUR FISIK PUISI “KANGEN” KARYA W. S RENDRA - Deri Saputra; Sandi Ferdiansyah; Yusep Ahmadi F; Rosi Rosi (IKIP Siliwangi, 2018)
Literary work is the representative or outpouring of the heart of an author, can be poured in the form of oral and written. Poetry is the disclosure of ideas, ideas, or feelings of the heart using figurative language. Writing poetry is usually used to criticize or express an event. In poetry there is a physical structure and an inner structure. The author chose the poem by W. S Rendra entitled